Democratic inclusion Rainer Bauböck in dialogue - Bauböck, Rainer (Critical Powers, 2018)
This book addresses the major theoretical and practical issues of the forms of citizenship and access to citizenship in different types of polity, and the specification and justification of rights of non-citizen immigrants as well as non-resident citizens. It also addresses the conditions under which norms governing citizenship can legitimately vary. The book discusses the principles of including all affected interests (AAI), all subject to coercion (ASC) and all citizenship stakeholders (ACS). They complement each other because they serve distinct purposes of democratic inclusion. The book proposes that democratic inclusion principles specify a relation between an individual or group that has an inclusion claim and a political community that aims to achieve democratic legitimacy for its political decisions and institutions. It contextualizes the principle of stakeholder inclusion, which provides the best answer to the question of democratic boundaries of membership, by applying it to polities of different types. The book distinguishes state, local and regional polities and argues that they differ in their membership character. It examines how a principle of stakeholder inclusion applies to polities of different types. The book illustrates the difference between consensual and automatic modes of inclusion by considering the contrast between birthright acquisition of citizenship, which is generally automatic, and naturalization, which requires an application.